The educator’s dilemma: balancing AI advancements with ethical concerns in assessments for higher education / Syamsul Nor Azlan Mohamad and Nadia Hanin Nazlan - Mohamad, Syamsul Nor Azlan; Nazlan, Nadia Hanin (UiTM Press, 2024)
In the rapidly changing landscape of higher education, Artificial Intelligence (AI) has emerged as an instrument with the potential to transform traditional pedagogical methodologies, particularly in the context of academic assessments. While the incorporation of AI can improve the objectivity, scalability, and personalization of assessments, it also raises challenges and concerns that require a thorough investigation. This study provides an empirical analysis of the status of AI integration within higher education assessment. A survey of academically diverse educators from various institutions of higher education was conducted to examine four dimensions: 1) the pace and methods of AI adoption in assessments; 2) ethical concerns tied to fairness, bias, and data privacy; 3) educators’ digital competence in effectively utilizing AI tools; and 4) educators’ overall receptivity and openness towards the prospect of further AI advancements in assessment. Preliminary findings indicate a growing interest in AI-based educational tools, along with a demand for rigorous training and ethical standards for their equitable application. In addition to shedding light on the educational incorporation of AI, this study lays the groundwork for future research, policies, and best practices. As higher education teeters on a technological precipice, it becomes increasingly important to comprehend educators’ AI perspectives. This research aims to enrich global discourse by employing AI’s potential in higher education responsibly and creatively.